Hydrological Consequences of Timber Harvesting in Landscape Zones of Siberia - Alexander Onuchin; Tamara Burenina; Igor Pavlov (Environments, 2017)
Despite a large number of publications covering various aspects of the influence of climatic factors on runoff, this direction in hydrological research acquires a new meaning in connection with global climate change and the increase in anthropogenic press on river systems. The authors of this work focused on the impact of anthropogenic factors on river runoff. Many rivers of Siberian taiga drain areas have experienced a dramatic land-cover change, with a decrease in overall forest area and a relative increase in deciduous trees. Land cover change in forest catchments impact water balance and accordingly, river flow. The study areas, the West Sayan and Northern Angara regions located in Central Siberia, are now a mosaic of forest regeneration sites including both post-human and post-fire regeneration patterns. Data of our own hydrological experiments conducted on clear cuts of different ages and reference materials for regular hydrological observations were analyzed. Dynamics of river flow under influence of timber harvesting were studied for 11 river basins in different landscape zones of Siberia. The studies showed that, in Siberia, forest cover changes lead to either reduction of, or increase in water yield depending on forest structure and climate. Dynamics of river flow after forest logging differ for continental and humid climates. Where precipitation is excessive, water yield increases twice that of control plots during the first several post-cutting years, due to reduction of transpiring phytomass. It takes 30–40 years and sometimes even over 50 years, depending on forest succession trajectories, for water yield to recover to the pre-cutting level. In an extremely continental climate, extensive forest cutting results in decreasing water yield during the first post-clearcutting years, because wind activity increases and enhances snow evaporation on vast clear cuts. Water yield exhibited an average annual decrease of 0.5–1.0 mm during the first two decades after cutting, i.e., until when clear cuts began to ...